Understanding human perception by human-made illusions - Carbon, Claus-Christian (Frontiers in Human Neuroscience, 2014)
It may be fun to perceive illusions, but the understanding of how they work is even more stimulating and sustainable: They can tell us where the limits and capacity of our perceptual apparatus are found—they can specify how the constraints of perception are set. Furthermore, they let us analyse the cognitive sub-processes underlying our perception. Illusions in a scientific context are not mainly created to reveal the failures of our perception or the dysfunctions of our apparatus, but instead point to the specific power of human perception. The main task of human perception is to amplify and strengthen sensory inputs to be able to perceive, orientate and act very quickly, specifically and efficiently. The present paper strengthens this line of argument, strongly put forth by perceptual pioneer Richard L. Gregory (e.g., Gregory, 2009), by discussing specific visual illusions and how they can help us to understand the magic of perception.